CD146 is a potential immunotarget for neuroblastoma. Issue 11 (30th September 2021) - Obu, Satoshi; Umeda, Katsutsugu; Ueno, Hiroo; Sonoda, Mari; Tasaka, Keiji; Ogata, Hideto; Kouzuki, Kagehiro; Nodomi, Seishiro; Saida, Satoshi; Kato, Itaru; Hiramatsu, Hidefumi; Okamoto, Tatsuya; et al.
Abstract: Neuroblastoma, the most common extracranial solid tumor of childhood, is thought to arise from neural crest‐derived immature cells. The prognosis of patients with high‐risk or recurrent/refractory neuroblastoma remains quite poor despite intensive multimodality therapy; therefore, novel therapeutic interventions are required. We examined the expression of a cell adhesion molecule CD146 (melanoma cell adhesion molecule [MCAM]) by neuroblastoma cell lines and in clinical samples and investigated the anti‐tumor effects of CD146‐targeting treatment for neuroblastoma cells both in vitro and in vivo. CD146 is expressed by 4 cell lines and by most of primary tumors at any stage. Short hairpin RNA‐mediated knockdown of CD146, or treatment with an anti‐CD146 polyclonal antibody, effectively inhibited growth of neuroblastoma cells both in vitro and in vivo, principally due to increased apoptosis via the focal adhesion kinase and/or nuclear factor‐kappa B signaling pathway. Furthermore, the anti‐CD146 polyclonal antibody markedly inhibited tumor growth in immunodeficient mice inoculated with primary neuroblastoma cells. In conclusion, CD146 represents a promising therapeutic target for neuroblastoma. Abstract : Targeting CD146 inhibits in vitro proliferation of neuroblastoma (NB) cells and in vivo growth of NB tumors. Exposure of NB cells to the anti‐CD146 antibody led to a significant reduction in survival and anchorage‐independent growth. Intraperitoneal injection of the anti‐CD146 antibody into immunodeficient mice for 50 d led to a significant inhibition of tumor growth.